Fighting MRSA Infections in Hospital Care: How Organizational Factors Matter. (22nd June 2016) - Salge, Torsten Oliver; Vera, Antonio; Antons, David; Cimiotti, Jeannie P.
Abstract : Objective: To identify factors associated with methicillin‐resistant Staphylococcus aureus (MRSA) bloodstream infections at the level of the hospital organization. Data Sources: Data from all 173 acute trusts in the English National Health Service (NHS). Study Design: A longitudinal study based on trust‐level panel data for the 5‐year period from April 2004 to March 2009. Fixed effects negative binominal and system generalized method of moment models were used to examine the effect of (i) patient mix characteristics, (ii) resource endowments, and (iii) infection control practices on yearly MRSA counts. Data Collection: Archival and staff survey data from multiple sources, including Public Health England, the English Department of Health, and the Healthcare Commission, were merged to form a balanced panel dataset. Principal Findings: MRSA infections decrease with increases in general cleaning (−3.52 MRSA incidents per 1 standard deviation increase; 95 percent confidence interval: −6.61 to −0.44), infection control training (−3.29; −5.22 to −1.36), hand hygiene (−2.72; −4.76 to −0.68), and error reporting climate (−2.06; −4.09 to −0.04). Conclusions: Intensified general cleaning, improved hand hygiene, additional infection control training, and a climate conducive to error reporting emerged as the factors most closely associated with trust‐level reductions in MRSA infections over time.